Placement of a lumen‐apposing metal stent using the water‐filling technique from an endoscopic nasocystic drainage catheter to walled‐off necrosis with less liquid component. Issue 4 (22nd March 2022) - Takahashi, Kosuke; Yasuda, Ichiro; Nakao, Kazuhiko
Abstract : Watch a video of this article.